Bone : Crown of Horns. - Smith, Jeff, 1960 Feb. 27- (New York : Graphix, 2009)
After stepping into a ghost circle Thorn is urged to locate the Crown of Horns, and sets off on a quest with Fone Bone to traipse through the sacred grounds of dragons, with the hope of returning with the only thing that can save everyone and everything she holds dear.
Maps on endpapers in trade bdg.
Voice of Youth Advocates (V.O.Y.A.)
4.1
3-6
3-6
Keywords: Cousins -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Cousins -- Fiction; Fantasy